Method for preparing copper element doped nickel-iron-manganese precursor material and sodium battery positive electrode material thereof

By optimizing the complexing process and using gallate compounds, combined with microcomplexing and cyclone separation technology, the problems of long preparation period of the precursor of the positive electrode material of sodium ion battery are solved and poor product uniformity are poor, and a sodium battery positive electrode material with excellent morphology and performance are prepared.

CN119841360AActive Publication Date: 2025-04-18ZHONGYE-CHANGTIAN INT ENG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510008430.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-18
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The precursors of the existing sodium ion battery positive electrode material have long preparation cycles and poor product uniformity, resulting in high production costs and poor product morphology.

Method used

By optimizing the complexing process, combining gallate compounds as antioxidants, and using microcomplexing operations and cyclone separation technology, copper-doped nickel-ferromanganese precursor materials are prepared, which improves the product's phase uniformity and particle size uniformity.

Benefits of technology

It has achieved the preparation of high-efficiency and low-cost sodium battery positive electrode materials, the product has excellent morphology and performance, and the recycling performance has also been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841360A_ABST
    Figure CN119841360A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a copper-doped nickel-iron-manganese precursor material and a sodium battery positive electrode material thereof, which comprises the following steps: adding a specific amount of complexing agent into a mixed metal salt solution in advance to prepare a micro-complexed mixed metal salt solution, so that the concentration of free metal ions is reduced to a certain extent; the release speed of metal ions is slowed down, the possibility of quickly generating hydroxide and quickly oxidizing the hydroxide is reduced, and the stability of the preparation process is improved. When copper ions are doped, the problem that copper hydroxide is incompatible can be solved. According to the preparation method disclosed by the invention, a complex process is optimized and a special anti-oxidation measure is combined, so that the multi-element precursor material which is uniform in phase, uniform in particle size and excellent in morphology and the corresponding sodium-ion battery positive electrode material are prepared; in addition, the method has the advantages of short preparation process, low cost, simplicity and convenience in operation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of battery electrode materials, and in particular to a method for preparing a copper-doped nickel-iron-manganese precursor material and a sodium battery positive electrode material thereof, belonging to the technical field of sodium battery electrode material preparation. Background Art

[0002] In recent years, lithium-ion batteries have been favored by the market due to their high energy density. However, with the widespread use of clean energy, the demand for energy storage batteries is growing. The high cost of lithium-ion batteries and the scarcity of lithium resources are becoming more and more obvious. The global shortage of lithium resources has restricted the sustainable development of lithium batteries. Studies have found that sodium-ion batteries have a similar working principle to lithium-ion batteries. Compared with lithium-ion batteries, sodium-ion batteries have the advantages of abundant synthetic raw materials, low production costs, high energy density, high voltage platform and excellent comprehensive performance. Domestic and foreign scholars generally recognize that it is the most promising ideal capacitor to replace lithium-ion batteries. Nickel-iron-manganese ternary positive electrode material, as a lower-cost positive material for sodium-ion batteries, is based on the classic sodium-ion positive electrode material NaNi 0.5 Mn 0.5 O2 system, which reduces the interlayer spacing by introducing low-cost iron ions. It has the advantages of inhibiting solvent co-embedding, enhancing cycle stability, and being more cost-effective and environmentally friendly. + The continuous transition metal sliding and Na + Vacancy ordering, layered transition metal oxides Na x MO2 materials will undergo a crystal phase transition accompanied by a significant change in the unit cell volume, and the change in the unit cell volume will cause the collapse of the positive electrode material structure, reducing the material's recycling performance. The use of electrochemically inactive cations for heterogeneous ion substitution can improve the material's recycling performance, but the incorporation of inactive elements will lead to a decrease in the material's specific capacity. At present, when using the coprecipitation method to prepare copper-doped precursors, copper phase separation is prone to occur, that is, copper hydroxide and nickel-iron-manganese hydroxide are incompatible, resulting in larger product lattice defects, poor morphology, and more impurities.

[0003] In addition, the study also found that the preparation of undoped nickel-iron-manganese layered hydroxide (type 111) mainly adopts liquid phase coprecipitation method. However, due to the large difference in the solubility product of the hydroxides of the three ions of nickel, iron and manganese, it is difficult to implement coprecipitation. Therefore, a complexing agent should be added during the reaction to reduce the concentration of free nickel ions and manganese ions in the solution to make it close to the concentration of free iron ions, thereby ensuring the coprecipitation of the three ions. And because Fe 2+ Easily oxidized to Fe by air 3+ , Fe 3+The pH of the precipitation is very low, so it is necessary to prevent it by adding antioxidants and ensuring an inert atmosphere. The preparation effect of the ternary hydroxide will seriously affect the electrochemical properties of the subsequently synthesized sodium-containing ternary oxide precursor. During the preparation and production process, the reaction conditions, including the type of precipitant. The concentration of the complexing agent, the speed of the stirring paddle, etc. will affect the precipitation effect, including the particle size, tap density, and microscopic morphology of the precipitated particles. At present, the main method for preparing this kind of ternary precursor on the market is: 1. First, prepare a base liquid with a certain ammonia concentration and pH, and add an antioxidant and pass nitrogen into it. The antioxidants used are mostly sodium sulfite and sodium thiosulfate; 2. Then, the prepared mixed metal salt solution and the alkaline solution containing the complex are added dropwise to the reactor; 3. The ternary precursor is obtained by setting the speed and temperature of the reactor and reacting for a period of time. The production method of this type of ternary hydroxide is relatively cumbersome, and the uniformity of the obtained samples is insufficient, and the product morphology needs to be improved. The shortcomings of this type of process are: 1) Since sodium sulfite and sodium thiosulfate are strong bases and weak acid salts, their alkalinity in water will affect the pH control of the precipitation process to a certain extent, and excessive addition of sulfite will lead to a large amount of sodium sulfate in the initially prepared product, increasing the difficulty of subsequent impurity removal. 2) This process cycle is relatively long, including nucleation period, passivation period and growth period. The long production cycle will generate higher production costs. 3) The particle size uniformity of the product prepared by this production process is poor, and there are many fine grains, which leads to the problem of agglomeration and compaction of the prepared product after drying. Summary of the invention

[0004] In view of the problems in the prior art that the existing sodium ion battery positive electrode material precursor has a long preparation cycle and poor product uniformity, the present invention provides a method for preparing a copper-doped nickel-iron-manganese precursor material and a method for preparing a corresponding sodium battery positive electrode material. By optimizing the complexation process and combining special antioxidant measures, a multi-element precursor material with uniform product phase, uniform particle size and excellent morphology and a corresponding sodium ion battery positive electrode material are prepared. At the same time, it also has the advantages of short preparation process, low cost, simple operation, etc.

[0005] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows:

[0006] According to a first embodiment of the present invention, a method for preparing a positive electrode material for a sodium battery is provided:

[0007] A method for preparing a copper-doped nickel-iron-manganese precursor material, the method comprising:

[0008] 1) First, add deoxygenated water, antioxidant, precipitant and dispersant into the reaction container and start stirring, then introduce protective gas and heat, and finally add complexing agent and mix well to obtain reaction base liquid.

[0009] 2) The copper salt solution, the nickel salt solution, the ferrous salt solution and the manganese salt solution are mixed to obtain a mixed metal salt solution, and then a complexing agent is added to the mixed metal salt solution to obtain a micro-complexed mixed metal salt solution.

[0010] 3) adding the micro-complexed mixed metal salt solution obtained in step 2) to the reaction base solution in step 1) to carry out a reaction.

[0011] 4) After the reaction of step 3) for a period of time, the coarse particle product in the reaction system is separated and aged. After the aging is completed, the product is filtered, washed and dried in sequence to obtain the copper-doped nickel-iron-manganese precursor material.

[0012] Preferably, in step 1), the antioxidant is one or more of methyl gallate, ethyl gallate, propyl gallate, isopropyl gallate, butyl gallate, tert-butyl gallate, and gallic acid.

[0013] Preferably, in step 1), the antioxidant is added in an amount such that the system concentration is no more than 0.05 mol / L, preferably 0.02 to 0.045 mol / L.

[0014] Preferably, in step 1), the precipitating agent is a base, preferably sodium hydroxide.

[0015] Preferably, in step 1), the amount of precipitant added is such that the pH of the system is 9 to 13, preferably 10 to 12 (the concentration of the precipitant is about 0.4 to 0.6 mol / L).

[0016] Preferably, in step 1), the dispersant is polyethylene glycol and / or polyvinyl alcohol, preferably polyethylene glycol and / or polyvinyl alcohol having an average molecular mass of 800 to 8000, more preferably one or more of polyethylene glycol (1000), polyethylene glycol (1500), polyethylene glycol (2000), polyethylene glycol (4000), polyethylene glycol (6000), polyvinyl alcohol (1788), and polyvinyl alcohol (2488).

[0017] It should be noted that the numerical value in the brackets represents the average molecular weight of the polymer, for example, polyethylene glycol (1000) represents polyethylene glycol with an average molecular weight of about 1000. These substances can be purchased from the market. For example, polyethylene glycol (1000), polyethylene glycol (1500), polyethylene glycol (2000), polyethylene glycol (4000), polyethylene glycol (6000), etc. can be purchased from Shanghai Donghui Chemical Technology Co., Ltd., Nantong Hesai New Materials Co., Ltd., or Jiangsu Hai'an Petrochemical Plant, etc. Polyvinyl alcohol (1788) and polyvinyl alcohol (2488) can be purchased from Jinan Hongke Chemical Technology Co., Ltd., Zhengzhou Jiajie Chemical Products Co., Ltd., or Henan Chuangxiang Chemical Products Co., Ltd., etc.

[0018] Preferably, in step 1), the dispersant is added in an amount such that the system concentration is no greater than 0.05 mol / L, preferably 0.02 to 0.04 mol / L.

[0019] Preferably, in step 1), the complexing agent is one or more of ammonia water, citric acid, oxalic acid and tartaric acid.

[0020] Preferably, in step 1), the complexing agent is added in an amount such that the system concentration is no more than 1 mol / L, preferably 0.3 to 0.8 mol / L.

[0021] Preferably, in step 1), the protective gas is an inert gas and / or nitrogen, preferably nitrogen. The flow rate of the protective gas is not less than 80 mL / min, preferably 90 to 150 mL / min.

[0022] Preferably, in step 1), the stirring rate is not less than 100 rpm, preferably 200-600 rpm.

[0023] Preferably, in step 1), the heating is to heat the system to 40-70°C, preferably 45-65°C.

[0024] Preferably, in step 2), the copper salt is one or more of copper sulfate, copper nitrate, and copper chloride. The nickel salt is one or more of nickel sulfate, nickel nitrate, and nickel chloride. The ferrous salt is one or more of ferrous sulfate, ferrous nitrate, and ferrous chloride. The manganese salt is one or more of manganese sulfate, manganese nitrate, and manganese chloride. Preferably, the molar ratio of nickel ions, copper ions, manganese ions, and ferrous ions in the mixed metal salt solution is (1-x): x: 0.8-1.2: 0.8-1.2, wherein 0≤x≤0.3.

[0025] It should be noted that in the preferred embodiment of the present invention, for example, when the molar ratio of nickel ions, copper ions, manganese ions, and ferrous ions is (1-x): x: 0.8-1.2: 0.8-1.2, if the amount of copper salt added is x = 0, it is to prepare the non-doped 111-type nickel-iron-manganese precursor material and continue to prepare the corresponding 111-type sodium battery positive electrode material. In the present invention, the metal salt used in the precipitation process is mainly its hydrate, for example, nickel sulfate salt includes anhydrous nickel sulfate and hydrated nickel sulfate, and other metal salts also include anhydrous salts and hydrated salts.

[0026] Preferably, in the micro-complexed mixed metal salt solution, the system concentration of the complexing agent is ≤0.03 mol / L, preferably 0.015 to 0.025 mol / L.

[0027] Preferably, in step 3), the amount of the micro-complexed mixed metal salt solution added is such that the concentration of the mixed metal salt in the reaction system is 0.2 to 0.5 mol / L, preferably 0.25 to 0.45 mol / L.

[0028] Preferably, in step 3), the reaction time is not less than 1 h, preferably 3 to 12 h.

[0029] Preferably, in step 4), the separation is cyclone separation. The particle size range of the coarse particle product is not less than 10 microns.

[0030] In the present invention, the molecular formula of the copper-doped nickel-iron-manganese precursor material can be expressed as: Ni 1 / 3- x Cu x Fe 1 / 3 Mn 1 / 3 (OH)2·0.5H2O, where 0≤x≤0.3.

[0031] According to a second embodiment of the present invention, a method for preparing a positive electrode material for a sodium battery is provided:

[0032] A method for preparing a positive electrode material for a sodium battery, the method comprising:

[0033] 1) First, add deoxygenated water, antioxidant, precipitant and dispersant into the reaction container and start stirring, then introduce protective gas and heat, and finally add complexing agent and mix well to obtain reaction base liquid.

[0034] 2) The copper salt solution, the nickel salt solution, the ferrous salt solution and the manganese salt solution are mixed to obtain a mixed metal salt solution, and then a complexing agent is added to the mixed metal salt solution to obtain a micro-complexed mixed metal salt solution.

[0035] 3) adding the micro-complexed mixed metal salt solution obtained in step 2) to the reaction base solution in step 1) to carry out a reaction.

[0036] 4) After the reaction of step 3) for a period of time, the coarse particle product in the reaction system is separated and aged. After the aging is completed, the product is filtered, washed and dried in sequence to obtain the copper-doped nickel-iron-manganese precursor material.

[0037] 5) The copper-doped nickel-iron-manganese precursor material is mixed with sodium salt and calcined to obtain a sodium ion battery positive electrode material.

[0038] Wherein: Step 1) to Step 4) are the same as the first implementation scheme.

[0039] Preferably, in step 5), the sodium salt is a combination of one or more of sodium carbonate, sodium bicarbonate and sodium acetate. The molar ratio of the copper-doped nickel-iron-manganese precursor material to the sodium salt is 1:0.501-0.505.

[0040] Preferably, in step 5), ethanol is added as a mixing agent when the copper-doped nickel-iron-manganese precursor material is mixed with the sodium salt.

[0041] Preferably, in step 5), the calcination temperature is 700-900° C., preferably 750-850° C. The calcination time is 3-48 hours, preferably 5-36 hours.

[0042] In the present invention, the molecular formula of the sodium battery positive electrode material can be expressed as: Na(Ni 1 / 3-x Cu x Fe 1 / 3 Mn 1 / 3 )O2, where 0≤x≤0.3.

[0043] In the present invention, gallic acid ester compounds are used as antioxidants in the reaction process. The antioxidants used in the current multi-element precursor material preparation process are mostly inorganic salts such as sodium sulfite and sodium thiosulfate, such as patent CN116886646A, and organic substances such as ascorbic acid, such as patent CN118108269A. The sulfite is alkaline in water and ascorbic acid is acidic, which will affect the precipitation process during the reaction. The gallic acid ester compounds proposed in the present invention are organic lipid substances and have strong free radical scavenging ability. A small amount of addition during the application process can show strong antioxidant ability, and it can be effectively removed by ethanol washing in the later stage, and almost no impurities are reflected. Compared with sulfites, thiosulfates and ascorbic acid, it is a better antioxidant.

[0044] In the present invention, the production cycle can be shortened by adding seed crystals during the mixed reaction process of the precursor material. At present, the production cycle of some precursor material preparation processes is relatively long, such as patent CN117800404, the longest production cycle reaches 210 hours. The present invention can first prepare grains with a particle size range of less than 3 microns as seed crystals, and then prepare the precursor, and the production cycle can be shortened to within 9 hours, that is, precursor particles with larger particle size and better morphology can be prepared.

[0045] In the present invention, before the reaction, a micro-complexation operation is performed on the mixed metal salt solution, which can improve the stability of the production process. That is, the present invention first adds a small amount of complexing agent to the mixed metal salt solution to form a micro-complexed mixed metal salt solution, thereby increasing the concentration of complexed ions in the solution and reducing the concentration of free ions. When the micro-complexed mixed metal salt solution is added dropwise to the reactor, the presence of complexed ions reduces the ability of ions to directly generate corresponding hydroxides, slows down the release rate of metal ions, prevents metal ions from quickly generating hydroxides and being quickly oxidized, improves the stability of the preparation process, and reduces the ferrous hydroxide generated during the reaction process to a certain extent; at the same time, when copper ions are doped, the incompatibility of copper hydroxide during the precipitation process is also improved, and the uniformity of element distribution in the particles is significantly improved.

[0046] In the present invention, by adding dispersants such as polyethylene glycol, polyvinyl alcohol, etc., a series of problems such as impure phase, severe compaction, and uneven particle size distribution of samples prepared by traditional processes are solved, the possibility of small hydroxide grains in the process quickly combining into large particles due to insufficient stirring is reduced, and the particle size uniformity of the prepared material is significantly improved.

[0047] In the present invention, the reaction is mainly divided into two stages, in which the first stage promotes the growth of fine grains on the seed crystal by adjusting the pH and ammonia concentration of the precipitation system; in the second stage, the product is classified by a cyclone separator, the coarse particles enter the next step, and the fine particles return to the reactor to continue the reaction, thereby shortening the reaction time and optimizing the product particle morphology. Under the action of a variety of improved conditions, the particle size, morphology and bulk density of the product prepared by the present invention are controlled, and a nickel-iron-manganese-containing precursor material that meets different industrial requirements can be produced.

[0048] Compared with the prior art, the beneficial technical effects of the present invention are as follows:

[0049] 1: The antioxidant used in the process of the present invention is a gallic acid lipid compound, which has less effect on the coprecipitation system than antioxidants such as sulfites, thiosulfates, and ascorbic acid. Moreover, due to its strong free radical binding ability, it can effectively play a protective role, and can be easily removed by alcohol washing in the later stage, and almost no impurities are introduced.

[0050] 2: The process of the present invention adds a specific amount of complexing agent to the mixed metal salt solution in advance to prepare a micro-complexed mixed metal salt solution, which reduces the concentration of free metal ions to a certain extent, slows down the release rate of metal ions, reduces the possibility of rapid generation of hydroxides and rapid oxidation, and improves the stability of the preparation process. When copper ions are doped, the problem of incompatibility of copper hydroxide can also be solved.

[0051] 3: The process of the present invention adopts a two-stage reaction concept. The first-stage reaction promotes the growth of fine grains on the seed crystals by adjusting the pH, ammonia concentration and other conditions of the precipitation system; the second-stage reaction is to classify the reaction products through a cyclone separator, and the coarse particles enter the next process, and the fine particles return to the reactor to continue the reaction, which greatly shortens the preparation cycle, and the prepared products have uniform particle size and regular morphology.

[0052] 4: The process of the present invention also uses dispersants such as polyvinyl alcohol to adjust the particle size. The addition of the dispersant limits the ability of small grains to quickly polymerize into large grains to a certain extent, so that the prepared precursor material has a good microscopic morphology and uniform particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 This is a SEM image of the copper-doped nickel-iron-manganese precursor material prepared in Example 1.

[0054] Figure 2 This is the XRD pattern of the copper-doped nickel-iron-manganese precursor material prepared in Example 1.

[0055] Figure 3 This is a diagram showing the composition ratios of the copper-doped nickel-iron-manganese precursor materials prepared in Example 1 and Example 12, respectively.

[0056] Figure 4 This is the XRD pattern of the sodium battery positive electrode material prepared in Example 1.

[0057] Figure 5 This is the SEM image of the sodium battery positive electrode material prepared in Example 1.

[0058] Figure 6 This is the XRD pattern of the nickel-iron-manganese precursor material prepared in Example 15.

[0059] Figure 7This is the SEM image of the nickel-iron-manganese precursor material prepared in Example 15.

[0060] Figure 8 This is the EDS image of the nickel-iron-manganese precursor material prepared in Example 15.

[0061] Fig. 9 This is the XRD pattern of the sodium battery positive electrode material prepared in Example 15.

[0062] Fig.10 This is the SEM image of the sodium battery positive electrode material prepared in Example 15.

[0063] Fig.11 The figure is an overall process flow chart of the method of the present invention. DETAILED DESCRIPTION

[0064] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.

[0065] Example 1

[0066] (1) Add 150 mL of deoxygenated water to a 500 mL reactor, add methyl gallate as an antioxidant, then add sodium hydroxide as a precipitant, and add polyvinyl alcohol (1788) as a dispersant; use a stirring paddle to stir at a uniform speed, and set the initial stirring speed to 300 rpm; wherein: the concentration of methyl gallate in the reactor is controlled to be 0.04 mol / L, the concentration of polyvinyl alcohol (1788) in the reactor is controlled to be 0.02 mol / L, and the amount of sodium hydroxide added to the reactor is controlled so that the pH value of the system is 11.5.

[0067] (2) nitrogen gas was introduced as protection, and the nitrogen flow rate was set to 80 mL / min; the reactor was heated until the temperature of the reaction system reached and stabilized at 55° C., and then ammonia water was added to the reactor as a complexing agent, and the ammonia concentration in the reactor was controlled to be 0.6 mol / L.

[0068] (3) Press Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+The molar ratio is 0.24:0.09:0.33:0.33. Nickel sulfate, copper sulfate, manganese sulfate and ferrous sulfate are dissolved in deoxygenated water to obtain a mixed metal salt solution, and then ammonia water is added to the mixed metal salt solution (the system concentration of ammonia water is controlled to be 0.03 mol / L) to obtain a micro-complexed mixed metal salt solution. Under the conditions of a stirring speed of 300 rpm and a temperature of 55°C, the micro-complexed mixed metal salt solution is added dropwise to the above-mentioned reactor at a rate of 12.5 mL / min (the amount of the micro-complexed mixed metal salt solution is such that the system concentration of the mixed metal salt in the reactor is 0.45 mol / L). After all the materials are added to the reactor, the current reaction conditions are maintained to continue the reaction for 6 hours to carry out the first stage of the reaction.

[0069] (4) After the first reaction stage is completed, the stirring speed and temperature of the system are kept unchanged to carry out the second stage of reaction. During this process, a portion of the solution (100 mL at a time, for 10 hours) is pumped into a cyclone separator for separation every 1 hour, and the separated coarse particles (particle size greater than 10 microns) are sent to the aging tank, and the remaining fine particles are returned to the reactor. After the second reaction stage is completed, the material in the aging tank is further aged for 6 hours, and then filtered and the solid product is washed with deoxygenated water and anhydrous ethanol in turn, and finally dried to obtain a copper-doped nickel-iron-manganese precursor material.

[0070] (5) The copper-doped nickel-iron-manganese precursor material prepared above and sodium carbonate are ground and mixed in a mortar in advance according to a molar ratio of 1:0.501, and alcohol is added during the process to make the materials evenly mixed, and then the evenly mixed materials are placed in an oven and dried at 100°C. Then, the dried sample is placed in a corundum crucible and placed in an electric furnace for calcination; the initial calcination temperature is set to 550°C, and after calcination for 5 hours, the temperature is slowly increased (15°C / min) to 850°C, and calcination is continued for 20 hours. After calcination is completed, the electric furnace is restored to room temperature and the sample is taken out, and the obtained sample is ground and sieved to obtain the positive electrode material of the sodium battery.

[0071] Example 2

[0072] (1) Add 150 mL of deoxygenated water to a 500 mL reactor, add methyl gallate as an antioxidant, then add sodium hydroxide as a precipitant, and add polyvinyl alcohol (1788) as a dispersant; use a stirring paddle to stir at a uniform speed, and set the initial stirring speed to 300 rpm; wherein: the concentration of methyl gallate in the reactor is controlled to be 0.04 mol / L, the concentration of polyvinyl alcohol (1788) in the reactor is controlled to be 0.02 mol / L, and the amount of sodium hydroxide added to the reactor is controlled so that the pH value of the system is 10.5.

[0073] (2) nitrogen gas was introduced as protection, and the nitrogen flow rate was set to 80 mL / min; the reactor was heated until the temperature of the reaction system reached and stabilized at 55° C., and then ammonia water was added to the reactor as a complexing agent, and the ammonia concentration in the reactor was controlled to be 0.6 mol / L.

[0074] (3) Press Ni 2+ , Cu 2+ , Mn 2+ , Fe 2+ The molar ratio is 0.24:0.09:0.33:0.33. Nickel sulfate, copper sulfate, manganese sulfate and ferrous sulfate are dissolved in deoxygenated water to obtain a mixed metal salt solution, and then ammonia water is added to the mixed metal salt solution (the system concentration of ammonia water is controlled to be 0.03 mol / L) to obtain a micro-complexed mixed metal salt solution. Under the conditions of a stirring speed of 300 rpm and a temperature of 55°C, the micro-complexed mixed metal salt solution is added dropwise to the above-mentioned reactor at a rate of 12.5 mL / min (the amount of the micro-complexed mixed metal salt solution is such that the system concentration of the mixed metal salt in the reactor is 0.45 mol / L). After all the materials are added to the reactor, the current reaction conditions are maintained to continue the reaction for 6 hours to carry out the first stage of the reaction.

[0075] (4) After the first reaction stage is completed, the stirring speed and temperature of the system are kept unchanged to carry out the second stage of reaction. During this process, a portion of the solution (100 mL at a time, for 10 hours) is pumped into a cyclone separator for separation every 1 hour, and the separated coarse particles (particle size greater than 10 microns) are sent to the aging tank, and the remaining fine particles are returned to the reactor. After the second reaction stage is completed, the material in the aging tank is further aged for 6 hours, and then filtered and the solid product is washed with deoxygenated water and anhydrous ethanol in turn, and finally dried to obtain a copper-doped nickel-iron-manganese precursor material.

[0076] (5) The copper-doped nickel-iron-manganese precursor material prepared above and sodium carbonate are ground and mixed in a mortar in advance according to a molar ratio of 1:0.501, and alcohol is added during the process to make the materials evenly mixed, and then the evenly mixed materials are placed in an oven and dried at 100°C. Then, the dried sample is placed in a corundum crucible and placed in an electric furnace for calcination; the initial calcination temperature is set to 550°C, and after calcination for 5 hours, the temperature is slowly increased (15°C / min) to 850°C, and calcination is continued for 20 hours. After calcination is completed, the electric furnace is restored to room temperature and the sample is taken out, and the obtained sample is ground and sieved to obtain the positive electrode material of the sodium battery.

[0077] Example 3

[0078] Example 2 was repeated except that methyl gallate as the antioxidant was replaced by ethyl gallate.

[0079] Example 4

[0080] Example 2 was repeated except that methyl gallate as the antioxidant was replaced by isopropyl gallate.

[0081] Example 5

[0082] Example 2 was repeated except that methyl gallate as the antioxidant was replaced by gallic acid.

[0083] Example 6

[0084] Example 2 was repeated except that polyvinyl alcohol (1788) as the dispersant was replaced by polyvinyl alcohol (2488).

[0085] Example 7

[0086] Example 2 was repeated except that polyvinyl alcohol (1788) as the dispersant was replaced by polyethylene glycol (1500).

[0087] Example 8

[0088] Example 2 was repeated except that polyvinyl alcohol (1788) as the dispersant was replaced by polyethylene glycol (4000).

[0089] Example 9

[0090] Example 2 was repeated except that the ammonia water as the complexing agent was replaced by citric acid.

[0091] Example 10

[0092] Example 2 was repeated except that the ammonia solution as the complexing agent was replaced by oxalic acid.

[0093] Embodiment 11

[0094] Example 2 was repeated except that the ammonia water as the complexing agent was replaced by tartaric acid.

[0095] Example 12

[0096] Example 2 was repeated, except that the amount of ammonia water added was controlled so that the system concentration of ammonia water in the micro-complexed mixed metal salt solution was 0.01 mol / L.

[0097] Embodiment 13

[0098] Example 2 was repeated, except that the amount of ammonia water added was controlled so that the system concentration of ammonia water in the micro-complexed mixed metal salt solution was 0.05 mol / L.

[0099] Embodiment 14

[0100] Example 2 was repeated, except that the time of the first stage reaction was controlled to 9 h.

[0101] Embodiment 15

[0102] (1) Add 150 mL of deoxygenated water to a 500 mL reactor, add methyl gallate as an antioxidant, then add sodium hydroxide as a precipitant, and add polyvinyl alcohol (1788) as a dispersant; use a stirring paddle to stir at a uniform speed, and set the initial stirring speed to 400 rpm; wherein: the concentration of methyl gallate in the reactor is controlled to be 0.045 mol / L, the concentration of polyvinyl alcohol (1788) in the reactor is controlled to be 0.02 mol / L, and the amount of sodium hydroxide added to the reactor is controlled so that the pH value of the system is 11.

[0103] (2) nitrogen gas was introduced as protection, and the nitrogen flow rate was set to 80 mL / min; the reactor was heated until the temperature of the reaction system reached and stabilized at 65° C., and then ammonia water was added to the reactor as a complexing agent, and the ammonia concentration in the reactor was controlled to be 0.6 mol / L.

[0104] (3) Press Ni 2+ , Mn 2+ , Fe 2+ The molar ratio is 1:1:1. Nickel sulfate, manganese sulfate and ferrous sulfate are dissolved in deoxygenated water to obtain a mixed metal salt solution, and then ammonia water is added to the mixed metal salt solution (the system concentration of ammonia water is controlled to be 0.04 mol / L) to obtain a micro-complexed mixed metal salt solution. Under the conditions of a stirring speed of 400 rpm and a temperature of 65°C, the micro-complexed mixed metal salt solution is added dropwise to the above-mentioned reactor at a rate of 12.5 mL / min (the amount of the micro-complexed mixed metal salt solution is such that the system concentration of the mixed metal salt in the reactor is 0.45 mol / L). After all the materials are added to the reactor, the current reaction conditions are maintained to continue the reaction for 6 hours to carry out the first stage of the reaction.

[0105] (4) After the first reaction stage is completed, the stirring speed and temperature of the system are kept unchanged to carry out the second stage of reaction. During this process, a portion of the solution (100 mL at a time, for 10 hours) is pumped into a cyclone separator for separation every 1 hour, and the separated coarse particles (particle size greater than 10 microns) are sent to the aging tank, and the remaining fine particles are returned to the reactor. After the second reaction stage is completed, the material in the aging tank is further aged for 6 hours, and then filtered and the solid product is washed with deoxygenated water and anhydrous ethanol in turn, and finally dried to obtain a 111 type copper element doped nickel iron manganese precursor material.

[0106] (5) The copper-doped nickel-iron-manganese precursor material prepared above and sodium carbonate are ground and mixed uniformly in a mortar in advance according to a molar ratio of 1:0.505, and alcohol is added during the process to make the materials uniformly mixed, and then the uniformly mixed materials are placed in an oven and dried at 100°C. Then, the dried sample is placed in a corundum crucible and placed in an electric furnace for calcination; the initial calcination temperature is set to 500°C, and after continuous calcination for 4 hours, the temperature is slowly increased (15°C / min) to 750°C, and calcination is continued for 20 hours. After calcination is completed, the electric furnace is restored to room temperature and the sample is taken out, and the prepared sample is ground and sieved to obtain the positive electrode material of the sodium battery.

[0107] Comparative Example 1

[0108] Example 2 was repeated except that methyl gallate as the antioxidant was replaced by sodium sulfite.

[0109] Comparative Example 2

[0110] Example 2 was repeated except that methyl gallate as the antioxidant was replaced by sodium persulfate.

[0111] Comparative Example 3

[0112] Example 2 was repeated, except that the amount of ammonia water added was controlled so that the system concentration of ammonia water in the micro-complexed mixed metal salt solution was 0 mol / L.

[0113] Comparative Example 4

[0114] Example 2 was repeated, except that the amount of ammonia water added was controlled so that the system concentration of ammonia water in the micro-complexed mixed metal salt solution was 0.08 mol / L.

[0115] Comparative Example 5

[0116] Example 15 was repeated, except that the amount of ammonia water added was controlled so that the system concentration of ammonia water in the micro-complexed mixed metal salt solution was 0 mol / L.

[0117] Comparative Example 6

[0118] Example 15 was repeated, except that the amount of ammonia water added was controlled so that the system concentration of ammonia water in the micro-complexed mixed metal salt solution was 0.08 mol / L.

[0119] Comparative table of product performance of each embodiment and comparative example:

[0120]

[0121]

[0122] It can be seen from the above table that the sodium battery positive electrode materials prepared by the copper-doped nickel-iron-manganese precursor material and the undoped nickel-iron-manganese precursor material prepared by the embodiments of the present invention have good discharge specific capacity and excellent cycle efficiency (i.e., 1C discharge specific capacity retention rate), and are significantly better than the sodium battery positive electrode materials prepared in Comparative Examples 1 and 2.

Claims

1. A method for preparing a copper-doped nickel-iron-manganese precursor material, characterized in that: The method includes: 1) firstly add deoxygenated water, antioxidant, precipitant and dispersant into a reaction container and start stirring, then introduce protective gas and heat, and finally add complexing agent and mix well to obtain reaction base liquid; 2) mixing a copper salt solution, a nickel salt solution, a ferrous salt solution, and a manganese salt solution to obtain a mixed metal salt solution, and then adding a complexing agent to the mixed metal salt solution to obtain a micro-complexed mixed metal salt solution; 3) adding the micro-complexed mixed metal salt solution obtained in step 2) to the reaction base solution in step 1) to carry out a reaction; 4) After the reaction of step 3) for a period of time, the coarse particle product in the reaction system is separated and aged; after the aging is completed, it is filtered, washed and dried in sequence to obtain the copper-doped nickel-iron-manganese precursor material.

2. A method for preparing a positive electrode material for a sodium battery, characterized in that: The method includes: 1) firstly add deoxygenated water, antioxidant, precipitant and dispersant into a reaction container and start stirring, then introduce protective gas and heat, and finally add complexing agent and mix well to obtain reaction base liquid; 2) mixing a copper salt solution, a nickel salt solution, a ferrous salt solution, and a manganese salt solution to obtain a mixed metal salt solution, and then adding a complexing agent to the mixed metal salt solution to obtain a micro-complexed mixed metal salt solution; 3) adding the micro-complexed mixed metal salt solution obtained in step 2) to the reaction base solution in step 1) to carry out a reaction; 4) After the reaction of step 3) for a period of time, the coarse particle product in the reaction system is separated and aged; after the aging is completed, the product is filtered, washed and dried in sequence to obtain a copper-doped nickel-iron-manganese precursor material; 5) The copper-doped nickel-iron-manganese precursor material is mixed with sodium salt and calcined to obtain a sodium ion battery positive electrode material.

3. The method according to claim 1 or 2, characterized in that: In step 1), the antioxidant is one or more of methyl gallate, ethyl gallate, propyl gallate, isopropyl gallate, butyl gallate, tert-butyl gallate, and gallic acid; Preferably, in step 1), the antioxidant is added in an amount such that the system concentration is no more than 0.05 mol / L, preferably 0.02 to 0.045 mol / L.

4. The method according to any one of claims 1 to 3, characterized in that: In step 1), the precipitant is a base, preferably sodium hydroxide; Preferably, in step 1), the amount of the precipitant added is such that the pH of the system is 9-13, preferably 10-12.

5. The method according to any one of claims 1 to 4, characterized in that: In step 1), the dispersant is polyethylene glycol and / or polyvinyl alcohol, preferably polyethylene glycol and / or polyvinyl alcohol having an average molecular weight of 800 to 8000, more preferably one or more of polyethylene glycol (1000), polyethylene glycol (1500), polyethylene glycol (2000), polyethylene glycol (4000), polyethylene glycol (6000), polyvinyl alcohol (1788), and polyvinyl alcohol (2488); Preferably, in step 1), the dispersant is added in an amount such that the system concentration is no greater than 0.05 mol / L, preferably 0.02 to 0.04 mol / L.

6. The method according to any one of claims 1 to 5, characterized in that: In step 1), the complexing agent is one or more of ammonia, citric acid, oxalic acid, and tartaric acid; Preferably, in step 1), the complexing agent is added in an amount such that the system concentration is no more than 1 mol / L, preferably 0.3 to 0.8 mol / L.

7. The method according to any one of claims 1 to 6, characterized in that: In step 1), the protective gas is an inert gas and / or nitrogen, preferably nitrogen; the flow rate of the protective gas is not less than 80 mL / min, preferably 90 to 150 mL / min; and / or In step 1), the stirring rate is not less than 100 rpm, preferably 200 to 600 rpm; In step 1), the heating is to heat the system to 40-70°C, preferably 45-65°C.

8. The method according to any one of claims 1 to 7, characterized in that: In step 2), the copper salt is one or more of copper sulfate, copper nitrate, and copper chloride; the nickel salt is one or more of nickel sulfate, nickel nitrate, and nickel chloride; the ferrous salt is one or more of ferrous sulfate, ferrous nitrate, and ferrous chloride; the manganese salt is one or more of manganese sulfate, manganese nitrate, and manganese chloride; preferably, the molar ratio of nickel ions, copper ions, manganese ions, and ferrous ions in the mixed metal salt solution is (1-x): x: 0.8-1.2: 0.8-1.2, wherein 0≤x≤0.3; Preferably, in the micro-complexed mixed metal salt solution, the system concentration of the complexing agent is ≤0.05 mol / L, preferably 0.02-0.04 mol / L.

9. The method according to any one of claims 1 to 8, characterized in that: In step 3), the amount of the micro-complexed mixed metal salt solution added is such that the concentration of the mixed metal salt in the reaction system is 0.2 to 0.5 mol / L, preferably 0.25 to 0.45 mol / L; and / or In step 3), the reaction time is not less than 1 hour, preferably 3 to 12 hours; and / or In step 4), the separation is cyclone separation; the particle size of the coarse particle product is not less than 10 microns.

10. The method according to claim 2, characterized in that: In step 5), the sodium salt is a combination of one or more of sodium carbonate, sodium bicarbonate, and sodium acetate; the molar ratio of the copper-doped nickel-iron-manganese precursor material to the sodium salt is 1:0.50-0.

52. Preferably, in step 5), ethanol is added as a mixing agent when the copper-doped nickel-iron-manganese precursor material is mixed with the sodium salt; In step 5), the calcination temperature is 700-900° C., preferably 750-850° C.; the calcination time is 3-48 hours, preferably 5-36 hours.

Citation Information

Patent Citations

  • Nickel-iron-copper-manganese precursor and preparation method thereof, positive electrode material, positive electrode and battery

    CN116621235A

  • Sodium-ion battery precursor, sodium-ion battery positive electrode material and preparation method of sodium-ion battery positive electrode material

    CN118289836A

  • Nickel-iron-manganese-copper quaternary positive electrode material as well as precursor, preparation method and application thereof

    CN118877958A

  • Positive electrode material and preparation method therefor, and sodium-ion battery

    WO2024060761A1

  • Sodium-ion battery positive electrode precursor, preparation method therefor, and use thereof

    WO2024239458A1